PENGARUH VISUAL MERCHANDISING DAN STORE ATMOSPHERE TERHADAP IMPULSIVE BUYING KONSUMEN KKV DP MALL SEMARANG - Aninda Cahya Fatihah; Bulan Prabawani; Apriatni E Prihatini (Universitas Diponegoro, 2025)
Impulsive buying is spontaneous purchasing activities consumers, which are influenced by several factors, including visual merchandising and store atmosphere. These two strategies provide stimuli for consumers, thereby increasing impulsive buying. The objective of this study is to analyze the impact of visual merchandising and store atmosphere on impulsive buying. This research is an explanatory study, using non-probability sampling techniques, resulting in 97 samples from consumers KKV DP Mall Semarang. Data was collected through a questionnaire using Likert scale, Microsoft Excel and SmartPLS 4 software were employed for data analysis. The results indicate that all items in the questionnaire are valid and reliable. It was found that visual merchandising has positive and significant effect on impulsive buying, with a categorization of 60%, indicating high level of attractiveness. The store atmosphere variable has positive and significant effect on impulsive buying, with a categorization of 57%, indicating high level of comfort. Both visual merchandising and store atmosphere together have positive and significant effect on impulsive buying, with a categorization of 74%, indicating very high level. This study suggests that companies should improve product signage and promotions to make more visible to consumers and provide more lighting in areas that consumers have complained about